Learning Analytics : A Bottom-up Approach to Enhancing and Evaluating Students' Online Learning : Final Report. - Fisher, Josie; Valenzuela, Fredy-Roberto; Whale, Sue (Office for Learning and Teaching, 2014)
Final report from a project that explored the potential for enhancing students' learning experiences by utilising data from the learning management system (LMS) in an innovative way to inform teaching practice including direct interactions between educators and students. In particular the project aimed at determining the value of real time, personalised interventions through analysis of student behaviour within the LMS (e.g., increased student engagement), subsequent performance in assessment tasks, reduced attrition, increased student satisfaction, and higher success rates. The project focused on distance education students enrolled in core or compulsory subjects in the Business School at the University of New England.